Understanding the brain uptake and permeability of small molecules through the BBB: A technical overview. Issue 8 (August 2021) - Chowdhury, Ekram Ahmed; Noorani, Behnam; Alqahtani, Faleh; Bhalerao, Aditya; Raut, Snehal; Sivandzade, Farzane; Cucullo, Luca
The brain is the most important organ in our body requiring its unique microenvironment. By the virtue of its function, the blood-brain barrier poses a significant hurdle in drug delivery for the treatment of neurological diseases. There are also different theories regarding how molecules are typically effluxed from the brain. In this review, we comprehensively discuss how the different pharmacokinetic techniques used for measuring brain uptake/permeability of small molecules have evolved with time. We also discuss the advantages and disadvantages associated with these different techniques as well as the importance to utilize the right method to properly assess CNS exposure to drug molecules. Even though very strong advances have been made we still have a long way to go to ensure a reduction in failures in central nervous system drug development programs.